Penentuan Kadar Etanol Pada Sampel Minuman dengan Metoda HPLC Menggunakan Fasa Gerak Asetonitril dan Buffer Fosfat - Nailul Rahmi; Budhi Oktavia; Nazulis Z (Departemen Kimia FMIPA UNP, 2013)
Alcoholic beverage is a drink containing ethanol. Ethanol is a psychoactive substance and its consumption causes loss of consciousness. All types of alcohol are essentially toxic, especially if consumed in excess, such as ethanol. According to BPOM limit of the use of alcohol in drinks are ± 1% - 5%. Ethanol content analysis in this study using HPLC method with condition UV-Vis using a mobile phase of acetonitrile: phosphate buffer (5: 95) pH 6 at 220nm wavelength detector and the use of stationary phase Zorbax Rx C18 ODS column. The result of this method is retention time for ethanol 1.68 minutes. The aplication of the method for determination of ethanol on the drinks from the market for 5 different samples was tested. The sample consists of 3 types of alcoholic beverage production factory/industrial, and 2 types of alcoholic beverages produced household. With adition standard techniques on samples was obtained ethanol adduct levels in 2 samples are 20.416% and 3.80%